Thermodynamics of a rotating black hole in minimal five-dimensional gauged supergravity. (4th August 2015) - Grunau, Saskia; Neumann, Hendrik
Abstract: In this article we study the thermodynamics of a general non-extremal rotating black hole in minimal five-dimensional gauged supergravity. We analyse the entropy-temperature diagram and the free energy. Additionally we consider the thermodynamic stability by calculating the specific heat, the isothermal moment of inertia tensor and the adiabatic compressibility.